PENGARUH KESEPAKATAN KERJA BERSAMA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS DRIVER MAXIM DI KOTA KUPANG - Kaho, Adelita Throci; Fanggidae, Rolland E.; Riwu, Yonas Ferdinand; Timuneno, Tarsisius (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
ABSTRACK THE EFFECT OF COLLECTIVE AGREEMENTS AND WORK MOTIVATION ON THE PRODUCTIVITY OF MAXIM DRIVERS IN KUPANG CITY By Adelita Throci Kaho Supervised by Rolland E. Fanggidae dan Yonas Ferdinand Riwu This study aims to describe collective bargaining agreements, work motivation, and driver productivity, as well as to determine the effect of collective bargaining agreements and work motivation on the productivity of Maxim drivers in Kupang City. This study uses a quantitative approach with an associative research type. Data collection techniques were carried out by distributing questionnaires to 96 Maxim drivers in Kupang City as respondents. The collected data was then processed and analyzed using SPSS statistical software. The data analysis techniques used in this study included descriptive analysis and inferential analysis. The results of the study based on descriptive analysis show that the achievement values of collective bargaining agreements and work motivation are in the high category, while the achievement value of Maxim driver productivity in Kupang City is in the very high category. The results of inferential analysis show that: (1) Collective bargaining agreements have a significant effect on driver productivity; (2) Work motivation has a significant effect on driver productivity; and (3) Simultaneously, both variables have a significant effect on driver productivity in Kupang City with an adjusted R square value of 0.856, which shows that the percentage contribution of the independent variable (X) to the dependent variable (Y) is 85.6%, and the rest is influenced by other variables not included in this study. Keywords: Collective Labor Agreement, Work Motivation, Productivity.